2012
DOI: 10.1134/s0021894412020113
|View full text |Cite
|
Sign up to set email alerts
|

Local nonsimilarity solution for the impact of the buoyancy force on heat and mass transfer in a flow over a porous wedge with a heat source in the presence of suction/injection

Abstract: Combined heat and mass transfer in free, forced and mixed convection flows along a porous wedge with internal heat generation in the presence of uniform suction or injection is investigated. The boundary-layer analysis is formulated in terms of the combined thermal and solute buoyancy effect. The flow field characteristics are analyzed using the RuugeKutta-Gill method, the shooting method, and the local nonsimilarity method. Due to the effect of the buoyancy force, power law of temperature and concentration, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Muhaimin and Kandasamy [2] exhibited an examination tends to the magnetic effects and chemical reaction over a wedge with porosity. After that Muhaimin et al [3] found the local non-similar solution for the chemical reactions with Mhd, mixed convection and suction/injection. Furthermore non-Newtonian fluids are discussed with different effects presented through [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Muhaimin and Kandasamy [2] exhibited an examination tends to the magnetic effects and chemical reaction over a wedge with porosity. After that Muhaimin et al [3] found the local non-similar solution for the chemical reactions with Mhd, mixed convection and suction/injection. Furthermore non-Newtonian fluids are discussed with different effects presented through [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%